Si/Ge–WSi2 composites: Processing and thermoelectric properties. (1st October 2015) - Mackey, Jon; Dynys, Frederick; Sehirlioglu, Alp
Graphical abstract: Abstract: Thermoelectric nano-composites composed of a Si/Ge matrix with WSi2 nano-precipitates were investigated and reductions in lattice thermal conductivity as large as 40% (compared to a benchmark silicide free sample) have been achieved. Additionally, samples exhibited enhanced figure of merit over that of classic state-of-the art Si/Ge, improvements as large as 30% were obtained for both p-type and n-type samples. Samples were prepared from powder metallurgic techniques; mechano-chemical alloying in a planetary mill combined with spark plasma sintering for densification. Thermoelectric properties and microstructure of the specimens were investigated in relationship to processing conditions and composition. The nano-composites investigated in this work provide both a viable enhancement mechanism with greater thermal stability and an experimental benchmark for theoretic work on silicide inclusions in Si/Ge matrix. This experimental work verifies the prospect to enhance figure of merit, and demonstrates that achieving uniform WSi2 nano-inclusion is a technical challenge using powder processing approach.